2019
DOI: 10.5713/ajas.18.0645
|View full text |Cite
|
Sign up to set email alerts
|

Variability of laying hen behaviour depending on the breed

Abstract: Objective For many generations, most species of farm animals have been subjected to intense and strictly targeted selection for improvement of their performance traits. This has led to substantial changes in animal anatomy and physiology, which resulted in considerable differences between the current animal breeds and their wild ancestors. The aim of the study was to determine whether there is breed-specific variability in behaviour as well as differences in emotional reactivity and preferences of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 22 publications
3
33
0
Order By: Relevance
“…The correlation coefficient was only slightly higher than 0.2; yet, it indicates that birds with a higher level of stress may need a longer time before the occurrence of tonic immobility. Concurrently, previous studies showed that tonic immobility was more difficult to achieve by excitable birds with increased emotional reactivity (Kozak et al 2019). This reaction may also be used as an indirect indicator the stress level in hens.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The correlation coefficient was only slightly higher than 0.2; yet, it indicates that birds with a higher level of stress may need a longer time before the occurrence of tonic immobility. Concurrently, previous studies showed that tonic immobility was more difficult to achieve by excitable birds with increased emotional reactivity (Kozak et al 2019). This reaction may also be used as an indirect indicator the stress level in hens.…”
Section: Discussionmentioning
confidence: 81%
“…Birds experiencing negative emotions would not show interest in the surrounding objects (Hocking et al 2001;Rodenburg et al 2003;de Haas et al 2013). The birds' behaviour in MOFT can be linked to negative or positive emotions (Kozak et al 2019), but the level of stress cannot be assessed based on the hens' reactions observed in the test. The behavioural response to a specific stimulus may be analogous in a situation of stress and in a situation when the HPA axis is not activated (Cockrem and Silverin 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It appears that birds' environmental needs may vary not only between species but also between breeds [3] and individuals of the same breed [4]. Previous investigations [3,5] have demonstrated that hens from three different breeds (green-legged partridge-Zk, Polbar-Pb, and Leghorn-Lg) kept in environments as identical as possible not only differed in the level of activity, emotional arousal, or degree of curiosity, but also preferred different enrichments of the environment, which collectively resulted in a different level of stress in the birds [5]. The Zk breed showed interest in objects that allowed scratching and searching, i.e., the birds preferred a container filled with finely shredded straw and woodchips as well as insect larvae but ignored a feed container, shelter box, or mirror.…”
Section: Introductionmentioning
confidence: 99%
“…Both breeds had a higher level of stress than the Zk chicks. The authors reported that the living environment fulfilled the needs of the Zk breed only, but failed to satisfy the needs of the Lg hens [3,5]. The birds were kept on bedding and thus the need of the Zk chickens to scratch and search was satisfied.…”
Section: Introductionmentioning
confidence: 99%